A preliminary study: An agent-based spatial simulation of human-coastal environment interaction in coastal urban tropical area - Hasti Widyasamratri; Al Aswad (International Conference on Coastal and Delta Areas, 2017)
Reported, 65% of Java island population are living in coastal area where one of the most affected areas on climate change. Disaster related to hydrological cycles such as flooding caused by tidal is the most frequent happen in the low area zone as well as Semarang city in Central Java province. Many process impacted tidal flood: land subsidence, sea level rise, and coastal land use change as a consequences of population pressure. It will getting worse when heavy rainfall is occur. Predicted, 2672, 2 Ha of coastal area at Semarang city will inundate caused by 16 cm sea level rise due to global warming impact. By this fact, coastal community is the most vulnerable group due to the flood. This paper is a preliminary study to simulate the interaction of humancoastal environment to response, adapt and mitigate the tidal flood through agent-based modelling (ABM) within spatial concept. ABM frameworks have been portrayed to function well in a socioenvironment context, modelling efforts for coupled human-coastal environment system that described as a process-based design framework. In this research, human actions are interpreted as an aggregate social response to stimuli from the physical system with both aspects being explicitly modelled at the scale of emergence of the hydrological phenomenon in coastal areas. The natural (coastal-hydrology) system is set, in modelling terms, through physical (tidal, land subsidence, land use change) models; the response of human units (settlements, fisherman, industry communities etc.) is then studied as a reactive mechanism to physical model output, such as tidal flood. In the other word, ABM is an empirical methods for building agent decision models in spatial planning. Keywords: agent-based model, coastal environment, human interaction, spatial planning.